La política de ventas al crédito y su incidencia en la situación económico - financiera de la empresa servicios y llantas Beda del distrito de Trujillo año 2015 - Beltrán Reyna, Flor de María (2017)
The present research work has as main objective to determine the incidence that have sales policies to credit in the economic and financial situation of the company BEDA SERVICES AND TIRES, as well as to determine which there are the risks to which the company is exhibited for not applying or implementing in an efficient way its credit politics. For the development of the present investigation was used the descriptive method, collecting and presenting in a systematic way the information obtained from the company, as are the Financial Statements, clients in default portfolio, uncollectible accounts as well as interviews with the head of the area of sales, head of collections and the general accountant; in order to analyse the situation of the same based on real data. After analyzing the obtained results it was concluded that to be a company that performs almost all its sales to credit is not implemented efficiently its lending policies, which are very simple and not put limits to grant a credit, which is affecting in a negative way in their economic and financial situation, mainly reflected in the high level of late payments from customers and the low level of liquidity that has to meet its obligations to third parties, so seen in the need to have recourse to external financing and compromise its heritage. So it is advisable to optimize the current credit policies and its application in the management of sales.